DIFFUSION BEHAVIOR OF KETOPROFEN THROUGH CHITOSAN-ALGINATE MEMBRANES - Purwantiningsih Sugita; Rini Siswati Asnel; Budi Arifin; Tuti Wukirsari (Universitas Gadjah Mada, 2010)
Chitosan-alginate membrane diffusion behavior has been investigated for its application in drugs delivery system. Ketoprofen diffusion behavior assay were performed at 37 and 42 °C to membrane thickness (h) and donor cell concentration of ketoprofen variations (A). The results showed that equilibrium concentrations (Cs) of ketoprofen equation was 27.0087 + 0.09067T - 1.7499h + 0.1030A + 0.0161h2 - 0.0022A2 + 0.0040Th - 0.0018TA + 0.0095hA. The value of Cs was closer to the expected therapy concentration at 50 and 75 mg/L with thin membrane (10-34 μm). Based on Higuchi equation, the model for J and D were J = 11.0849 - 0.2713T - 0.3132h - 0.7461Cs - 0.0096A - 0.0001h2 - 0.0131Cs2 + 0.0002A2 + 0.0084Th + 0.0275TCs - 0.0018TA - 0.0059hCs + 0.0021hA + 0.0037CsA with R2 = 97.9% and D = -12.5000 + 0.2266T + 0.1313h + 0.1538Cs + 0.1200A - 0.0009h2 + 0.0240 Cs2 - 0.0009A2 + 0.0015Th - 0.0150 TCs - 0.0011TA - 0.0096hCs + 0.0004hA + 0.0039CsA with R2 = 98.7%, respectively. The two dimensional contour maps of J versus A and h, both at 37 and 42 °C, showed an increasing of J value as A, h, or T increased.